A reassessment of money demand in Nigeria - Moses K. Tule; Usman M. Okpanachi; Patricks Ogiji; Nurudeen Usman (CBN Journal of Applied Statistics, 2018)
This paper re-examines broad money (M2) demand and its stability in Nigeria using the Autoregressive Distributed Lag (ARDL) bounds testing procedure. First, the results indicate that a stable long-run relationship exists between M2 and its determinants including GDP, stock prices, foreign interest rates and real exchange rate. Furthermore, stock prices showed a significant and positive effect on the long-run broad money demand, which in some ways reflect increased 'financialization' and integration of the Nigerian economy into the global economic system. Overall, the findings of this study lend credence to the continued relevance of the broad money aggregate, M2, as a benchmark for monetary policy implementation in Nigeria.
Keywords: E41; C42; 330; Money Demand; Stability; ARDL Model; Bounds Test